Analysis of Accounting Information System Implementation Cash Expenditures for Official Travel Costs at The Large Hall of South Sulawesi Teacher Drivers - Febriana, Triah; Dunakhir, Samirah; S, Masnawaty (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
This research aims to find out how the cash disbursement accounting information system for official travel costs is implemented at the South Sulawesi Teacher Mobilization Center. The variable for this research is the Cash Expenditure Accounting Information System for Official Travel Expenses. Data collection was carried out using documentation, observation and interviews to complete the required information. The analysis method was carried out using descriptive analysis, namely by implementing the cash disbursement accounting information system of the South Sulawesi Teacher Mobilization Center with theory according to Mulyadi. The results of this research indicate that the system used by the South Sulawesi Teacher Mobilization Center is the Institutional Level Financial System (SAKTI) which is in accordance with applicable regulations. The suitability of cash disbursement procedures according to Mulyadi (2018) with the implementation of the cash disbursement accounting information system for official travel costs at the South Sulawesi Teacher Mobilization Center, there are slight differences in the documents and records used, but for the parties involved in the cash management process there are several different functions and agencies already have flowcharts for official travel cash expenditures so that they can be considered quite effective.